Interpretation: faith and despair - Blesa, Túa (Tropelías: Review of Literary Theory and Comparative Literature, 2021)
The hermeneutical theory of Mario Valdés takes as reference the works of Miguel de Unamuno, who considered the act of reading an interchange between his I and the whole of the remaining readers. Literature becomes, then, an open dialogue with the other, a process in which the reader builds his own personality taking as reference the multiplicity of perspectives that offers the hermeneutics of the literary work. A task marked by the faith and the despair: faith because the reader’s confidence in appropiating that multiplicity of perspectives in order to build his own self, but also despair because the interminability of the task, the consciousness of the impossibility of accomplishing it because of the relativity of the interpretative act.